Epidemiological aspects of malaria notifications in Piauí (Research, Society and Development, 2021)
Malaria is a parasitic infectious disease, with a great impact on global health, caused by parasites of the genus Plasmodium. It is transmitted through a vector, the female infected with the Anopheles mosquito or popularly known as the nail mosquito, therefore, it is not a contagious disease and is not transmitted from person to person. This study aimed to describe the epidemiological situation of malaria in Piauí between the years 2015 and 2019. An epidemiological survey of malaria cases in Piauí was carried out between the years 2015 to 2019 through the SINAN-DATASUS platforms, using the variables sex, age group, race, protozoan species and municipalities with notification. The results found were expressed in Excel tables. It was observed that the cities with the highest number of cases were Luzilândia and Teresina, in addition, the disease spread more among browns and in men aged 20-39 years. Furthermore, the species most found in the parasitological results was Plasmodium falciparum. Piauí does not have a significant number of cases, but it is still necessary to strengthen surveillance and control and prevention of cases through rapid and effective measures.